Differential expression of miRNAs in the body wall of the sea cucumber Apostichopus japonicus under heat stress - Chang, Mengyang; Li, Bin; Liao, Meijie; Rong, Xiaojun; Wang, Yingeng; Wang, Jinjin; Yu, Yongxiang; Zhang, Zheng; Wang, Chunyuan (Frontiers in Physiology, 2022)
MicroRNAs, as the post-transcriptional regulation of genes, play an important role in development process, cell differentiation and immune defense. Apostichopus japonicus is an important cold-water species, known for its excellent nutritional and economic value, which usually encounters heat stress that affects its growth and leads to significant economic losses. However, there are few studies about the effect of miRNAs in heat stress in sea cucumbers. In this study, high-throughput sequencing was used to analyze miRNA expression in the body wall of sea cucumber between control group (CS) and heat stress group (HS). A total of 301 known miRNAs and 58 novel miRNAs were identified, of which 13 miRNAs were identified as significantly differentially expressed miRNAs (DEMs) in response to heat stress. A total of 16,563 target genes of DEMs were predicted, and 101 inversely correlated target genes that potentially regulated by miRNAs in response to heat stress of sea cucumbers were obtained. Based on these results, miRNA-mRNA regulatory networks were constructed. The expression results of high-throughput sequencing were validated in four of these DEMs and DEGs by quantitative real-time PCR. Moreover, pathway enrichment of target genes suggested that several important regulatory pathways may play an important role in the heat stress process of sea cucumber, including ubiquitin-mediated proteolysis, notch single pathway and endocytosis. These results will provide basic data for future studies in miRNA regulation and molecular adaptive mechanisms of sea cucumbers under heat stress.